The role of cardiac MRI in the diagnosis and management of sinus venosus atrial septal defect - Madhusudan Ganigara; David Tanous; David Celermajer; Rajesh Puranik (Wolters Kluwer Medknow Publications, 2014)
Sinus venosus atrial septal defects (SV-ASDs) are inter-atrial communications caused by a deficiency of the common wall between the superior or inferior vena cava and the right-sided pulmonary veins. The diagnosis can be challenging, especially in adults with delayed presentation. We present images that illustrate an example of the role of cardiac magnetic resonance imaging (CMRI) in the diagnosis and follow-up of a patient with SV-ASD.